Analysis of Product Marketing Strategies using SWOT and AHP Methods at PT Raya Utama - Vivian; Mardhatillah, Anggianika (Journal Knowledge Industrial Engineering (JKIE), 2021)
Raya Utama Travel is one of travel agency that is developing in Medan. problems that occur in Pt Raya Utama are since the establish of traveloka and the number of OTA system that are currently developing have made the company sales decreased. This research used the method of SWOT to know internal and external factor strategies in the company and followed by AHP to know what the priority strategies suit the most can be applied to the company. The result of this research obtained weighting IFE score of 2,88 while EFE obtained score weighting of 3,02. From SWOT matrixs formula obtained 3 strategies which from 3 will be choosen which one will be prioritize using AHP calculation. The result of AHP calculation showed that strategy alternative is from criteria product and strategy that can be applied to product development is changing company website program system, developing service quality, expanding and maintaining the market, increasing the types of online product, creating applications for company and frequent training for employee.